SPECTROPHOTOMETRIC DETERMINATION OF PYROCATHECOL AND PYROGALLOL BASED ON THEIR REDOX REACTION WITH IRON(III)/PHENANTHROLINE SYSTEM - Mudasir Mudasir; Mugiyanti Mugiyanti; Ngatidjo Hadipranoto (Indonesian Journal of Chemistry, 2002)
An analytical method for the spectrophotometric determination of some phenolic compounds, i.e.: pyrocathecol and pyrogallol based on their redox reaction with iron(III)-phenanthroline complex has been developed. These two compounds, in appropriate conditions, reduce iron(III)-phenanthroline complex to yield very stable and color-intense complex of iron(II)-phenanthroline, [Fe(phen)2]2+, whose concentration is equivalent to the amount of pyrocathecol or pyrogallol in the solution, and is easily detected by spectrophotometric method. Some parameters influencing the sensitivity of the determination were optimized. These included maximum absorption wavelength, pH of the solution, time and temperature of heatingand reagent to analyte minimum mole-ratio. Using the optimum conditions obtained, the analytical performance of the method was examined and the developed method was then applied to analyzed pyrocathecol and pyrogallol contents in several river water of Yogyakarta, Indonesia. Result of the study showed that the optimum conditions for the determination of pyrocathecol are as follows: maximum absorption wavelength (lmax) at 510 nm, pH of the solution = 4, heating time = 120 min, heating temperature = 70 0C and the minimum mole ratio of reagent to analyte is 8. On the other hand, the optimum conditions for the determination of pyrogallol are as follows: maximum absorption wavelength (lmax) at 510 nm, pH of the solution = 5, heating time = 90 min, heating temperature = 90 0C and the minimum mole ratio of reagent to analyte is 7. At the corresponding conditions of analysis, calibration curves for pyrocathecol and pyrogallol are linear in the range concentration of 0.00 - 0.16 ppm and 0.00 - 0.24 ppm, respectively. The correlation coefficients for both compounds were found to be higher than 0.998 and the detection limits went down below 0.07 ppm. It has been demonstrated that the developed method can be applied for the determination of pyrocathecol and pyrogallol contents in natural samples.